Partnership Management of Fishing Vessel of Nautica Study Program (Case Study at State Vocational High School 1 Pemangkat) - Tan Hero; Aswandi Aswandi; M. Chiar (STKIP Singkawang, 2018)
The Nautical fishing vessel study program is the most superior study program compared to the other four (4) Study Programs. The uniqueness of Nautical fishing vessel study program is a very prominent partnership with the business world that is able to establish cooperation with companies in Asia and Europe in the form of a dual system education and graduate distribution to the world work. This study aims to clearly describe the partnership management of the Nautical Fishing Vessel Study Program in SMKN 1 Mapping formulated in several research questions with the principles of planning and implementation of management. The approach used in this research is qualitative descriptive with case study research type namely 1) Data Reduction, done by reviewing all data obtained well through the interview; 2) Display Data, namely by systematize principal information with the theme and pattern that appears to be in accordance with the conclusions of data collected will be meaningful; 3) Taking conclusions and data on the summary of information data that appears in the Display data, simple data, meaning, solid conclusions are made. The data obtained in the study is processed qualitatively based on the answers obtained by way of describing the answer in the form of conclusion. Summaries conducted to conduct analysis of research findings among other: a) Understanding of the object between the first of the SMK and second party World business / industrial world; b) mutual agreement which is the initial stage of good cooperation between the parties concerned; c) joint actions to achieve the objectives of the partnership: mutual benefit between the two parties.